Addressing the Peri‐Wound Intact Skin of Hard‐To‐Heal Diabetic Foot Ulcers With Topical Red Deer Conditioned Media (PTT‐6TM) Skin Conditioner: A Case Series on Clinical Efficacy - Kimberley Leow; Leon Timothy Charles Alvis; Bradley Edmond Charles Yuen; Leighton Cheng; Shiqi Chiam; Siti Nurfarahdillah Binte Abdul Razak; Gerard Benjamin Evans; Kenneth Koh; Ivor Jiun Lim; Toan Thang Phan; Keng Lin Wong (Health Science Reports)
ABSTRACT Background and Aim The healing of diabetic foot ulcers (DFUs) can be hindered by the susceptibility of the surrounding intact skin to pro‐inflammatory proteases. A conditioned media, known as PTT‐6TM, derived from mesenchymal stem cells found in the lining of red deer umbilical cords, has been formulated to protect the intact peri‐wound skin of DFUs. The aim is to evaluate the clinical effectiveness of PTT‐6TM in managing peri‐wound intact skin in hard‐to‐heal DFUs. Methods Patients with DFUs that persisted for over 3 months were divided into two subgroups. The active wound group received standard‐of‐care treatment protocol followed by PTT‐6TM application around the peri‐wound area, while the maintenance wound group applied PTT‐6TM media over the healed wound site. Results Forty cases were recorded, of which 22 (55%) were included in the active wound group. The majority were male (75%, n = 30) and vast majority had cardiovascular risk factors, including diabetes mellitus (100%, n = 40), hyperlipidemia (82.5%, n = 33), and hypertension (77.5%, n = 31). Most patients had forefoot wounds (80%, n = 32) on the plantar aspect (82.5%, n = 33). The patients in the active wound group had chronic DFUs for a mean of 218 ± 201 days. Of those treated with PTT‐6™ media, 68.4% (n = 13) achieved complete wound healing within a mean duration of 69 ± 50 days. Additionally, most patients in the maintenance wound group remained ulcer‐free at 3 months (91.7%, n = 11) and 6 months (66.7%, n = 6). Conclusion The study results suggest that PTT‐6TM media may serve as an additional treatment modality for enhancing the microenvironment at the peri‐wound intact skin site. This could indirectly facilitate wound healing by preserving the integrity of the peri‐wound intact skin.